(untitled) (Research, Society and Development, 2023)
Objective: The high potential of digital technologies to reduce medication errors in patients hospitalized or under hospital care was explored in this investigation. The study identifies common types of medication errors and their probable causes. Furthermore, examines the technological innovation solutions available that have not yet been applied in this context, specifically the Internet of Things usage to reduce medication errors through a practical example. Methods: A rapid review was applied, exploring the papers from two databases. The analysis was limited to the period from 2017 to 2021, resulting in 147 articles from the VHL Regional Portal – Virtual Health Library and 257 articles from the PubMed database. Results: There were analyzed 40 studies. An error mapping related to the theme was made. Also, the technology application and their effectiveness were identified in the studies. According to the research, inattention or distraction due to the excessive journey of work was pointed out as the main reason that leads to medication errors with the systems employed. Conclusion: There are several opportunities to improve hospital procedures with new technological approaches. By implementing innovative technologies, hospital medication errors can be managed more efficiently and reduce costs and waste with errors medication.